Team Regulatory Focus and its Role for Idea Generation, Idea Implementation, and Innovative Performance: A Dynamic Perspective. (27th May 2021) - Hundeling, Maike; Auerswald, Max; Rosing, Kathrin
Abstract: In an experimental study, we explored the relationships between team regulatory focus and temporal patterns of innovative activities as well as innovative performance. We manipulated regulatory focus in 44 student teams and assessed idea generation and implementation activities over time based on video data. External raters assessed innovative performance. Latent growth curve models revealed that higher team promotion focus increased idea generation at the beginning of an innovative project but decreased this activity over time. High levels of idea generation at the beginning of a project were related to lower levels of originality, whereas a decline in idea generation over time was related to higher levels of originality. Unexpectedly, relationships between team prevention focus, idea implementation, and quality were not significant. Our findings contribute to a comprehensive perspective on team regulatory focus and innovation, emphasizing the importance of differentiating between activities and performance.